Forecasting Electricity Consumption And Its Relationship With Climate Change In Pekanbaru City - Zhafran, Fauzan; Miefthawati, Nanda Putri (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
Global warming which results in climate change resulting in an increase in air temperature and rainfall is a major problem in the world, especially Pekanbaru City. The significant increase in air temperature and rainfall recently has a close relationship with electrical energy consumption in Pekanbaru City. So forecasting air temperature, rainfall, and electricity consumption as well as the relationship between each of these variables is needed so that in the future society can adapt and mitigate. The aim of this research is to predict changes in air temperature, rainfall, and electricity consumption and to find out how much influence air temperature and rainfall have on electricity consumption in Pekanbaru City. In predicting related variables, the method used is decomposition model forecasting and to determine the relationship between each variable, multiple linear regression analysis is used. The graph of forecast results for 2023 – 2027 shows a decreasing trend in air temperature and electricity consumption, while rainfall experiences an increasing trend. The regression results show that the effect of changes in air temperature and rainfall simultaneously on electricity consumption is 3.5%, then the results of the F test and t-test show an insignificant effect of changes in air temperature and rainfall on electricity consumption.